Effectiveness of nano-herbal Phaleria macrocarpa on physiological evaluation in Rattus norvegicus - Simanjuntak, Leo; Rumahorbo, Cheryl Grace Pratiwi (Bulgarian Pharmaceutical Scientific Society, 2024)
Preeclampsia, a complex pregnancy disorder characterized by hypertension and proteinuria, poses significant risks to maternal and perinatal health. Despite extensive research, its etiology remains elusive. This study investigates the therapeutic potential of nano-herbal Phaleria macrocarpa , a medicinal plant known for its anti-inflammatory and antioxidant properties, in a rat model of preeclampsia. The study elucidates the formulation's effects through a multifaceted evaluation of physiological parameters, including blood pressure, organ weight, and complete blood counts. Pregnant rats were divided into five treatment groups (C-, C+, C1, T1, T2, and T3) and intraperitoneally injected with prednisone and 6% NaCl for 14 days to induce preeclampsia. Preeclamptic rats exhibited a blood pressure of 140/90 mmHg. C- served as the negative control and C+ as the positive control; C1 received nifedipine, while T1, T2, and T3 received varying doses of the herbal formulation. Blood pressure was measured on days 5, 13, and 20 of pregnancy, with a complete blood count and organ weight analyses conducted on the final treatment day. The results indicated significant differences among the three administered doses. The T3 group (720 mg/kg BW) exhibited noteworthy similarities to nifedipine. Implementing the T3 dosage demonstrated superior efficacy in preserving blood pressure, a complete blood profile, and organ health in preeclampsia rat models. Substantial reductions in diastolic blood pressure, changes in organ weights, and enhancements in hematological parameters supported these findings, underscoring the potential of Phaleria macrocarpa as both an antihypertensive and organ-protective agent.